Advancements in Multiple Myeloma Treatment: Insights from Clinical Trials in Asia - Ting Fang Tang; Chin Sum Cheong; Nur Adila Anuar; Won Fen Wong; Gin Gin Gan (Trends in Immunotherapy, 2025)
Multiple myeloma (MM) is one of the most common hematological cancers characterized by the abnormal expansion of clonal plasma cells, resulting in the secretion of abnormal monoclonal proteins and disruption of normal hematopoiesis in human bone marrow. Despite historically lower prevalence than in Western nations, an increasing incidence of MM has been noted in Asian countries. In recent years, the therapeutic landscape of MM has undergone a major transformation with the development of proteasome inhibitors (PIs) and monoclonal antibodies (mAbs), which have now emerged as cornerstones of treatment. PIs such as bortezomib, carfilzomib, and ixazomib selectively inhibit the proteasome, disrupting protein homeostasis in myeloma cells and inducing apoptosis. Bortezomib, the first-in-class PI, revolutionized MM therapy, while second-generation inhibitors like carfilzomib and ixazomib have improved potency and safety profiles. mAbs, including anti-CD38 agents (daratumumab and isatuximab) and the anti-SLAMF7 agent (elotuzumab), have markedly enhanced survival outcomes by specifically attacking myeloma cells and promoting immune-mediated destruction. Daratumumab, in particular, has shown exceptional efficacy both as monotherapy and in combination regimens, leading to its widespread adoption in frontline and relapsed/refractory MM (RRMM) settings. Other emerging therapies such as chimeric antigen receptor (CAR) T-cell therapy and bispecific antibodies are revolutionizing MM management. CAR T-cell therapy, particularly BCMA-targeted constructs, has yielded impressive clinical outcomes in RRMM but is limited by manufacturing challenges, toxicities, and durability of response. Bispecific antibodies, which simultaneously target myeloma cells and T cells, offer promising efficacy. Additionally, newer drug classes, including selective nuclear export inhibitors, histone deacetylase inhibitors, and novel small-molecule inhibitors, are being explored to overcome resistance mechanisms. This review provides a comprehensive overview of MM pathophysiology and disease progression, with a focus on the landscape of treatment strategies in Asian countries.